Mitigating the effects of exposure to violence against women : an educational perspective - Foss, Hugo (My University, 1988)
One hundred sixty-four female and one hundred twenty-four male undergraduate university students participated in an experiment designed to assess the role and / or value of education in mitigating the effects of exposure to violence against women. In order to assess the role of education some subjects were given type-written educational interventions (briefings) designed to dispel rape myths prior and / or subsequent to exposure to a written violent acquaintance-rape depiction, while other subjects received only the rape depiction and no intervention. The basic design of the experiment was a 2 x 2 x 2 factorial with gender and educational interventions (ie, Prebriefing and Debriefing) as the independent variables. Two additional control groups were created in order to explore the impact of the rape depiction. All subjects were required to complete a Sexual Attitudes Survey in which the dependent measures were embedded. The results indicated that subjects who received an educational intervention prior to the rape depiction significantly decreased their levels of rape myth acceptance and adversarial sexual beliefs in comparison to subjects who did not receive any educational intervention. Further significant results were found between the genders; across all conditons females, relative to males, were significantly less accepting of rape myths, interpersonal violence, and adversarial sexual beliefs. Females also expressed significantly greater sensitivity to the content of the rape depiction than males. The implications of the present data are discussed in terms of their impact on the direction of future research in establishing effective educational interventions.
Keywords: Pornography; Crimes against women; Violence in mass media Psychological aspects